Wavespeed measurement in buried water distribution pipes and its significance in leak location - Brennan, Michael [UNESP]; De Almeida, Fabricio; Joseph, Philip; Dray, Simon; Whitfield, Stuart (Trans Tech Publications, 2013)
To determine the location of leaks in buried water pipes, acoustic methods are often used. These have proven to be very effective in metallic pipes but have been problematic in modern plastic pipes. In this paper the reason why this is so is discussed together with some measurements that were made on a bespoke test rig built by South Staffs Water plc. A particular problem is the estimate of the wavespeed. Tables are frequently used for this purpose, but these are often inaccurate and this means that a leak cannot be located accurately. An in-situ measure of the wavespeed is thus preferable. In this paper it is shown that there are significant issues in obtaining an accurate estimate of the wavespeed when a leak is present in the system. A method is proposed that overcomes some of these problems, which is discussed and is demonstrated using some data from the bespoke test-rig. © (2013) Trans Tech Publications.
Keywords: Buried plastic pipes; Leak detection; Wavespeed estimate; Acoustic method; Leak locations; Metallic pipes; Test rigs; Water distribution pipes; Water pipes; Wavespeed; Damage detection; Plastic pipe; Water pipelines; Estimation